Intragroup variation in the Pre-Columbian Cuba population: A perspective from cranial morphology - Syutkina, Taisiya; Pérez, Mario Juan Gordillo; Hernández Godoy, Silvia Teresita; Antúnez, Carlos Arredondo; Rivero, Armando Rangel (Anthropological Review, 2021)
The paper aims to study intragroup variation inside the two pre-Columbian Cuban populations: the aceramic Archaic and the ceramic Taino groups, based on their cranial morphology. The latter applied artificial cranial deformation to all its members, so the groups are referred to as “non-deformed” and “deformed” samples here. Studies across different disciplines suggest evidence of cultural and biological diversity inside the non-deformed group, while local variations of applying the deforming device can be responsible for shape variation across the deformed group. Cranial metrics and non-metric cranial traits of the 92 crania of Cuban origin were analyzed, although the sample size varied between the analyses due to the incompleteness of the crania. Geometric morphometrics was applied to the deformed crania to study the shape variation across the sample. Three deformed crania from the Dominican Republic were analyzed together with the deformed Cuban sample to test the variability of the practice between the islands. Principal component analysis and the Mantel test did not reveal any geographic differences in the cranial metric traits. No morphological differences associated with the antiquity of materials could be seen either based on the available data. The principal component analysis of the Procrustes coordinates of the cranial vault outline in the lateral norm revealed continuous variability of cranial shapes from the ones with more flattened frontal and occipital bones to the more curved outlines, which is probably explained by individual variation. Non-metric traits variation revealed bilateral asymmetry in the expression of the occipito-mastoidal ossicles among the deformed crania. In conclusion, the study did not support assumptions about morphological diversity inside the studied samples or proved the impossibility of available craniological data to reflect possible intragroup differentiation at the moment.